Investigation on Cold Flow Properties of Biodiesel from Rubber Seed Oil, Palm Oil and its Blending - Ishak, Muhamad Faiz (Universiti Teknologi PETRONAS, 2012)
This research aims to discover the effects of mixing two types of biodiesel which are; biodiesel from rubber seed and biodiesel from palm oil, to the cold fiow properties of the biodiesel. The cold flow properties had always become the major problem for biodiesel as compared to petroleum based diesel due to its high amount of saturated fatty acid methyl esters (FAMEs) components (Joshi &Pegg, 2007). Both biodiesel are self produces by using optimum conditions available and mixed by desired ratio to discover which ratio of biodiesel from rubber seed and biodiesel from palm oil give the best flow properties. Fresh palm oil obtain from shop is used and it goes through a two step transesterification with 1:6 mole ratio of oil to methanol at 55°C and constantly mixed for 30 minute. 1%KOH by weight is used as catalyst and 70% of mixed KOH methanol solution is used on the first transesterification and the other 30%goesto the next. As for the rubber seed oil, crude palm oil from Vietnam is used and it goes through a series of esterification and transesterification. As for esterification, 1:13 mole ratio of oil to methanol is at 65°C and constantlymixed for 120 minute. This follows with transesterification, with mole ratio of 1:6.5 mole ratio of oil to methanol at 65°C and constantly mixed for 120 minute. The fatty acid methyl ester(FAME) content is analyze before mixed and 7 samples different mixed ratio of both biodiesel are obtain and ready for cold flow properties analysis. The cold flow properties measured are the cloud point and the cold filter plugging point. Other parameters that will be measured during the research arc densities, water content, and carboncontent of mixture of the two biodiesel. The result showsthat the sample which shows the best cold flow properties is sample POO which has cloud point of 4.2°C and cold flow plugging point of 0°C.